Marketing in the age of Google : your online strategy is your business strategy - Fox, Vanessa, 1972- (John Wiley & Sons, 2010)
"In this non-technical book for executives, business owners, marketers, and product managers, search engine strategy guru Vanessa Fox-who created Google's portal for site owners, Google Webmaster Central -explains what every marketer or business owner needs to understand about how search rankings work, how to use search to better understand your customers and attract new ones, how to develop a comprehensive search strategy for your business, and how to build execution of this strategy into the businesses processes. This isn't another book about paid search for advertisers. This book focuses on organic listings -- the unpaid results that receive 86% of searcher clicks."--Resource description page.